2010
DOI: 10.1136/jech.2009.101212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PM10 and O3 on infant mortality among residents in the Mexico City Metropolitan Area: a case-crossover analysis, 1997-2005

Abstract: Our results suggest that in the Mexico City Metropolitan Area, infants with lower SES (low to medium) are at higher risk of mortality when exposed to ambient PM(10) and O(3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…The influence of SES on mortality has also been examined in studies of infant mortality in Mexico. These studies found no association between O 3 concentrations and infant mortality regardless of SES measured using neighborhood-level indicators such as income or availability of public services (Carbajal-Arroyo et al 2011; Romieu et al 2004a); however, Carbajal-Arroyo et al (2011) reported evidence of a positive association for respiratory-related infant mortality in only the low-SES group.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of SES on mortality has also been examined in studies of infant mortality in Mexico. These studies found no association between O 3 concentrations and infant mortality regardless of SES measured using neighborhood-level indicators such as income or availability of public services (Carbajal-Arroyo et al 2011; Romieu et al 2004a); however, Carbajal-Arroyo et al (2011) reported evidence of a positive association for respiratory-related infant mortality in only the low-SES group.…”
Section: Resultsmentioning
confidence: 99%
“…Again, an effect of NO 2 was observed, but there was no evidence of an interaction with PM 2.5 . In contrast, a study of infant mortality in Mexico City observed that its association with PM 10 was heightened when high concentrations of ozone were also present (Carbajal-Arroyo et al, 2011). Finally, in a study of 29 European cities, Katsouyanni et al (2001) reported that cities with higher long-term average NO 2 demonstrated a greater effect of daily PM 10 on mortality than did cities with low average NO 2 .…”
Section: Epidemiologymentioning
confidence: 86%
“…Psychosocial factors or stressors were not examined in any study. Seven (58 %) found synergistic associations between environmental and SES factors for perinatal outcomes, whereby having lower SES appeared to potentiate the risk of air pollution [42,[44][45][46][48][49][50]. The five studies that found mixed or null joint associations between environmental and social exposures relied on archival data for exposures and outcome (e.g., birth registries, census) and/or used ecologic and cross-sectional designs [43,47,[51][52][53].…”
Section: Cognitive and Behavioral Outcomesmentioning
confidence: 94%
“…Perinatal Outcomes All 12 studies that considered the joint contribution of social and environmental exposures in relation to perinatal outcomes did so by aggregating birth data from national or regional registries and conducted case-crossover, spatial, ecologic, and multilevel studies [42][43][44][45][46][47][48][49][50][51][52][53] (Table 3). Eight focused on outcomes related to birth weight and being small for gestational age [43-46, 49, 51-53], five studied preterm birth [43,48,50,52,53], and two examined infant mortality [42,47].…”
Section: Cognitive and Behavioral Outcomesmentioning
confidence: 99%
See 1 more Smart Citation